Reducing stress of university students using music therapy - Wang, Xiao Heng (2015)
This project is designed to study the type of music which is the most effective in reducing stress of university students in terms of rhythms (Rock vs Classical), timbres ( Flute vs Violin vs Piano) and tunes (Standard vs Falling vs Rising). In order to examine the effects of different rhythms, timbres and tunes, 140 students were invited to take part in the experiment. They were asked to fill in a questionnaire first and then randomly assigned to one music group. All participants were required to perform a stressful mental arithmetic test prior to listening to the music in order to make them in a stressful condition before listening to the music. The results show that sedative music with a falling tune is the most effective music in stress reduction. As for the timbre, there does not exist significant differences, as long as the listener is familiar with the music, the stress level is likely to decrease. This project has significant implications for the practice of music therapy in clinics, as it provides convincing evidence for the usage of certain music in reducing stress of university students. And also, the conclusion of this project can be used in the daily life of university students for self-healing and self-adjustment when they feel stressed.